2006
DOI: 10.1128/mmbr.00027-06
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Protein Kinase PKR in Cell Biology: from Antiviral to Antiproliferative Action

Abstract: SUMMARY The double-stranded RNA-dependent protein kinase PKR is a critical mediator of the antiproliferative and antiviral effects exerted by interferons. Not only is PKR an effector molecule on the cellular response to double-stranded RNA, but it also integrates signals in response to Toll-like receptor activation, growth factors, and diverse cellular stresses. In this review, we provide a detailed picture on how signaling downstream of PKR unfolds and what are the ultimate consequences for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
739
2
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 703 publications
(762 citation statements)
references
References 404 publications
(475 reference statements)
11
739
2
10
Order By: Relevance
“…PKR, one of the several eIF2a kinases and a component of the interferonmediated antiviral response, participates in the innate immune response that protects host cells from virus infections by blocking translation of viral mRNAs (Samuel, 2001;Garcia et al, 2006). Many viruses have evolved various strategies to nullify this cellular response (Garcia et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…PKR, one of the several eIF2a kinases and a component of the interferonmediated antiviral response, participates in the innate immune response that protects host cells from virus infections by blocking translation of viral mRNAs (Samuel, 2001;Garcia et al, 2006). Many viruses have evolved various strategies to nullify this cellular response (Garcia et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…PKR is activated by binding to double-stranded RNA formed during viral replication; it phosphorylates the a-subunit of translation factor eIF2, resulting in inhibition of protein synthesis (Barber, 2005;Garcia et al, 2007). PKR has also been implicated in many additional cellular stress responses and corresponding signal transduction pathways, including the nuclear factor-kB and p38-mitogen-activated protein kinase pathways (reviewed by Barber, 2005;Garcia et al, 2006Garcia et al, , 2007. A major role for PKR has recently emerged in the control of apoptosis, following activation of the tumour-suppressor p53 pathway (Yoon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A major role for PKR has recently emerged in the control of apoptosis, following activation of the tumour-suppressor p53 pathway (Yoon et al, 2009). Inhibition of protein synthesis through eIF2a phosphorylation plays a considerable part in PKR activity (Scheuner et al, 2006;Lee et al, 2007), but other pathways are most likely also involved (Garcia et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This prevents viral replication and inhibits normal cell ribosome function, killing both the virus and the host cell if the response is active for a sufficient amount of time [6]. PKR cannot block the translation of some cellular and viral mRNAs bearing special features in their 5 0 untranslated regions [7]. PKR also affects diverse transcriptional factors such as interferon regulatory factor 1, STATs, p53, activating transcription factor 3, and NF-B [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…PKR also affects diverse transcriptional factors such as interferon regulatory factor 1, STATs, p53, activating transcription factor 3, and NF-B [8,9]. The extent and strength of the antiviral action of PKR are clearly understood by the findings that unrelated viral proteins of animal viruses have evolved diverse strategies to inhibit PKR action [7,10]. Knock-out mouse studies confirmed a role for PKR in antiviral innate immunity [11].…”
Section: Introductionmentioning
confidence: 99%